Bahasa Inggris - Supeno Supeno; Trapsilo Prihandono; I Ketut Mahardika; Sudarti Sudarti; Lailatul Nuraini (Postgraduate, University of Mataram, 2022)
Lesson study was a practical approach to improve the quality of instruction and use widely in professional development programs for teachers. This article presents an innovative approach to developing the instruction ability and skills of science teacher candidates when actual teaching practice in a classroom through lesson study. Based on the lesson study approach, science teacher candidates worked collaboratively to understand the curriculum and state the desired learning outcomes; design lesson plans; teach a common lesson in 4 different classrooms; and conduct reflection to share, discuss, and refine their lesson. The teaching abilities and skills are assessed based on knowledge of the subject matter, quality of lesson plans, and learning practices. The result showed that the lesson study approach was a vital structure that helped science teacher candidates improve their teaching skills and ability. The research result gives implications for development programs for science teacher candidates will be discussed in light of these findings. Â